The role of calcium score in evaluation of the advancing of ischemic heart disease - Tomaszewski, Michał; Kozioł, Maciej; Kozioł, Jadwiga; Zadrąg-Olko, Agnieszka; Piech, Piotr; Tomaszewski, Andrzej; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2017)
Introduction: Thanks to development of technology, new noninvasive techniques of coronary arteries evaluation, such as Multislice Computed Tomography (MSCT) were introduced. Nowadays tomographs are characterized by spatial and time resolution sufficient for reliable assessment of coronary arteries. Moreover, the dose of radiation taken by patient was substantially decreased. Two main methods of evaluation were introduced. Examination performed without contrast agent enables quantitive assessment of coronary arteries calcification by so called Agatston score. Another method performed after contrast injection is Computed Tomography Angiography (CTA) Goal: This studies purpose was to determine the role of Calcium Score in assessment of Coronary Arteries Disease (CAD) advancement Materials and methods: In this study the results of 100 consecutive patients (45% men, mean age 55 ± 8.9 years) were analyzed. All patients had a positive ECG stress test score. With a 64-row CT scan, coronary artery imaging of all patients was performed. The descriptive analysis of the group was based on information obtained from referrals issued by cardiologists to the MSCT. Analyzed parameters were: age, gender, indication for referral, Calcium Score and final diagnosis. Results: In most cases (84%) of patients with positive ECG stress test score, MSCT excluded significant changes in coronary arteries. Also, the correlation between Calcium Score and sex and diagnosis was proven. Conclusions: MSCT and Calcium Score enables to find patients without significant changes in coronary arteries and positive ECG stress test and to reduce the number of referrals to coronarography.